2013
DOI: 10.1007/s00127-013-0764-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic attributions and mental illness diagnosis: effects on perceptions of danger, social distance, and real helping decisions

Abstract: Consistent with genetic contingency theory, genetic attributions for schizophrenia, but not affective disorders, lead to greater desire for social distance via greater perceived dangerousness. Further, results suggest that genetic attributions decrease the likelihood of helping people with schizophrenia, but have no effect on the likelihood of helping people with affective disorders. These effects are partially accounted for by desired social distance from people with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…As far as specific aspects of schizophrenia are concerned, when considering causal beliefs, biogenetic and psychosocial causal attributions were expected to be the two extremes of a dimension, as found in previous studies [6,36,37]. Hypotheses were also made concerning relations between schizophrenia origins and possible treatments and of relations with a desire for social distance, perception of danger and general public avoidance of schizophrenic patients [3,[38][39][40]. Furthermore, a hypothesis was formulated that a latent structure, combining schizophrenia causal beliefs, social distance, perceived dangerousness and avoidance, should exist, also including possible schizophrenia treatments [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…As far as specific aspects of schizophrenia are concerned, when considering causal beliefs, biogenetic and psychosocial causal attributions were expected to be the two extremes of a dimension, as found in previous studies [6,36,37]. Hypotheses were also made concerning relations between schizophrenia origins and possible treatments and of relations with a desire for social distance, perception of danger and general public avoidance of schizophrenic patients [3,[38][39][40]. Furthermore, a hypothesis was formulated that a latent structure, combining schizophrenia causal beliefs, social distance, perceived dangerousness and avoidance, should exist, also including possible schizophrenia treatments [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Contact with PWD, moreover, was found to be associated with reduced fear towards people with this disorder, and also with lower perception of dangerousness and unpredictability towards PWS (35). It has been also found that students' attribution of a 5 mental disorder to biogenetic factors is associated with greater social distance, mediated by the perception of dangerousness, in schizophrenia but not in depression; and that genetic attribution decreases the likelihood of helping PWS but has no effect on the likelihood of helping PWD (36).…”
Section: Introductionmentioning
confidence: 99%
“…In research on mental illness, genetic and biologic causal attributions have been found to be associated with “prognostic pessimism” among affected individuals . Similarly, some mental illnesses are viewed by the general public as more serious and less treatable when they are perceived to have a genetic cause . However, the impacts of genetic causal attributions may vary among different disorders.…”
mentioning
confidence: 99%
“…7 Similarly, some mental illnesses are viewed by the general public as more serious and less treatable when they are perceived to have a genetic cause. 8,9 However, the impacts of genetic causal attributions may vary among different disorders. A qualitative study of individuals with four conditions (deafness/hearing loss, breast cancer, sickle cell disease, and cystic fibrosis) found that genetic attributions had both negative and positive psychosocial impacts that were shaped by the context of the lived experience of each condition.…”
mentioning
confidence: 99%